Ẓafarnāma-yi Khusrawī : Sharḥ-i ḥukmrawāyi-yi Sayyid Amīr Naṣrallāh Bahādur Sulṭān b. Ḥaydar - Sutūda, Manūchir, (Miras Maktoob, ISBN: 9789004365452., 2019)
Ẓafar-nāma is the title of a number of Persian works, in poetry or prose, mostly in glorification of some ruler or dynasty. As examples one could cite the Ẓafarnāmā-yi Tīmūrī (9th/15th cent.), the Ẓafarnāma-yi Shāh Jahān (11th/17th cent.), or the Ẓafarnāma-yi Kābūl (13th/19th cent.). The anonymous Ẓafarnāma-yi Khusrawī published here clearly stands in that tradition. Composed in 1279/1862-63, it was written with the purpose of recording the major events and achievements in the reign of the Manghit ruler of Bukhara, Amīr Sayyid Naṣrallāh b. Ḥaydar (reg. 1257-77/1841-60), preceded by an account of the happenings that led to his coming to power. The Manghits of the Khanate of Bukhara were a Turco-Mongolian dynasty that ruled over Transoxania between 1756 and 1920. The present work gives a detailed, insider account of many of the events that shaped the history of the region halfway the nineteenth century. As such, it is an invaluable and much-needed source of information.